College Event Management System / Muhammad Iqbal Iskak - Iskak, Muhammad Iqbal (2022)
Difficulty in registering for an event in college is a common problem faced by college residents. Having to collect physical stickers and keeping it safe is hard for students who are busy in their daily life. QR Code technology was an idea that can be implemented in this system as a registration method which help students to register for an event more quickly. Therefore, the objective of this project is to develop a web system called College Event Management System to read QR Code from students and manage all events in a database and to evaluate the effectiveness of the mobile application using Functionality Test and User Acceptance Test (UAT). Development methodology used in this project is Waterfall Model. It includes five phases which are requirement analysis phase, design phase, development phase, testing phase and documentation phase. The results from the test conducted shows that majority of the respondents are neutral in using College Event Management System. Some recommendation that can be done to improve the system is to create a profile for student to check on their registered events. Future works for this research is to create a mobile application that can be integrated with the system to enable user to have easier access to the system.